Structures and strategies for retaining an international pediatric cohort from birth: Lessons from The Environmental Determinants of Diabetes in the Young (TEDDY) study - Gesualdo, Patricia; Melin, Jessica; Karban, Rachel; Crouch, Claire; Killian, Michael; Hopkins, Diane; Adamsson, Annika; Stock, Joanna; Johnson, Suzanne Bennett; Baxter, Judith; TEDDY Study Group (Elsevier BV, 2025)
Background: Retention of study participants in observational studies is essential to maintaining the representativeness of the population, minimizing selection bias, and assuring sufficient statistical power. The aim of this report is to describe the structures and strategies used to retain participants in The Environmental Determinants of Diabetes in the Young (TEDDY) Study, an observational study of children at increased genetic risk for type 1 diabetes followed in an intense protocol with frequent clinic visits from birth until age 15.
Methods: A systematic review of methodologies used to retain research subjects identified four domains: barrier reduction strategies; community building strategies; follow-up/reminder strategies; and tracing strategies. Independent reviewers categorized the retention strategies implemented by the TEDDY Study into each of these domains. Strategies not fitting into any of these categories were placed into a fifth category unique to TEDDY.
Results: TEDDY identified over one hundred retention strategies used during the 15 years of follow-up; most could be categorized in these domains. Those unique to TEDDY included (1) study organization and structures to support retention; (2) efforts to meet the changing developmental needs of the TEDDY population, (3) implementation of efforts to address protocol challenges in real-time; and (4) employment of a re-engagement protocol for those who had dropped out of the study.
Conclusion: Pediatric cohort studies should include strategies, structures, and resources addressing retention at the study's initiation. It is recommended that child and parent engagement in addition to the developmental needs of the child be an integrated focus of all strategies. Putting mechanisms in place to address protocol and retention challenges in real time would facilitate effectively addressing challenges as they arise.
Trial registration: ClinicalTrials.gov Identifier: NCT00279318.